Peningkatan Kapasitas Produksi Bumbu Bali “Nepaon” Suka Wirang Desa Buki - I Ketut Putu Suniantara; Gede Suwardika; Agus Tatang Sopandi; Kadek Masakazu; I Gusti Ngurah Satria Wijaya (STMIK Royal, 2023)
The Balinese spice